Comparison of two puncture methods in the implantation of totally implantable venous access ports: a retrospective study - Fang, Kun; Li, Chang-Jia; Zhang, Jia-jun; Liu, Yu-Kun (Frontiers in Surgery, 2025)
BackgroundTotally implantable venous access ports (TIVAPs) are widely used for cancer patients requiring long-term chemotherapy. The classical procedure of vein puncture in the implantation of TIVAPs is to puncture by a needle and then make a skin incision to insert a guidewire and a dilator. The purpose of this study is to compare the effects of making a skin incision before vs. after TIVAP operation on the occurrence of complications.MethodsPatients with breast cancer were from the Affiliated Qingdao Central Hospital of Qingdao University. The participants were randomly assigned in to two groups with different puncture methods in the implantation of TIVAPs. The difference between two puncture methods were assessed by length of incision, procedure time, bleeding volume, extent of pain and appearance satisfaction after procedure. Multivariable linear regression was used to investigate the difference of complications between groups.ResultsA total of 300 patients with breast cancer were included in our study. The mean age of participants was 53.47 years. No significant differences were found between groups in length of incision, procedure time, and extent of pain. However, participants who received the incision before internal jugular vein puncture had less bleeding volume (p = 0.04) and were more satisfied with the appearance of their incision (p = 0.03).ConclusionWe present a method that makes the incision before vein puncture for guidewire and dilator insertion in TIVAD placement. This method may result in less bleeding and improved appearance for patients undergoing chemotherapy for cancer.